Factors Influencing the Selection of Self-Medication As an Alternative Treatment in Pharmacy Hashifah 02 Makassar City - Rina Asrina; Dian Hayati Ibrahim (Politeknik Sandi Karsa, 2021)
Self-medication is the step most used by the community in dealing with complaints or minor illnesses that are influenced by several factors, including economic factors, personal experience or suggestions from others. The purpose of this study was to determine the factors that influence the selection of self-medication as an alternative treatment at the Hashifah 02 Pharmacy, Makassar City. This research was conducted using a descriptive method using a questionnaire as a data collection tool. This research was conducted in September - October 2021 by distributing questionnaires to 87 people who came to the Hashifah 02 Pharmacy Makassar City and according to the criteria. The results showed that several factors that influenced the choice of self-medication, namely economic factors as much as 84%, personal experience as much as 77%, ease of obtaining products as much as 60%, lack of medical time as much as 64%, advice from other people as much as 56%, through advertising as much as 48%. , access to health services is minimal as much as 25%. So it can be concluded that the most influencing the choice of self-medication as an alternative treatment is the economic factor as much as 84%.